أهمية اكتساب مدقق الحسابات للمعرفة المتخصصة في تعزيز مصداقية التقارير المالية - فخر نواف; شلا محمد (Latakia University Journal - Economic and Legal Sciences Series, 2016)
Due to expansion of globalization and innovations in different fields of modern world, it became obliging for those interested in the profession of auditing to acquire specialized skill of a specific industrial sector prior to practicing their profession in order to realize the basic target of auditing process which is to cast credibility on financial information included in the financial lists which are the basic reference to those interested in investment decision making and other related parties. Research problem calls to answer two inquiries which are: - What is the importance for the auditor to prossessing specialized knowledge? - Will this serve to increase accuracy of financial reports? In order to answer these two questions became vital to emphasize the role of prossessing specialized experience which became necessary to the work of the auditor, and to confirm credibility of financial reports. We performed a field study that covered a sample of auditors practicing in Syria and the results of the field and theoretical studies confirm the need for the auditor to possess experience which is highly important in the degree of credibility of the audited financial reports. أسفرت المستجدات العالمية في شتى الميادين وانتشار ظاهرة العولمة إلى مطالبة المهتمين بشؤون مهنة التدقيق في الحسابات بضرورة حصولهم على المعرفة المتخصصة بقطاع صناعي معين أساسا لمزاولتهم العمل المهني, وذلك لتحقيق الهدف الأساسي من عملية التدقيق وهو إضفاء الثقة على المعلومات المالية التي تحتوي عليها القوائم المالية, التي تعتبر المرجع الأساس لمتخذي القرارات الاستثمارية وكافة الأطراف ذات المصالح. وتمثلت مشكلة البحث في الإجابة عن تساؤلين هما: ما هي الأهمية المتوخاة من امتلاك مدقق الحسابات للمعرفة المتخصصة؟, وهل تسهم تلك المعرفة في تعزيز دقة التقارير المالية؟ وللإجابة عن هذين التساؤلين تم التعريف بمفهوم المعرفة المتخصصة, وأهمية امتلاكها وارتباطها بعمل مدقق الحسابات, بالإضافة لدورها في تعزيز مصداقية التقارير المالية, فضلاً عن إجراء دراسة ميدانية شملت عينة من مدققي الحسابات المزاولين في الجمهورية العربية السورية. وجاءت نتائج الدراسة النظرية والميدانية لتشير إلى أهمية امتلاك مدقق الحسابات للمعرفة, ودورها في إضفاء المصداقية على التقارير المالية الخاضعة للتدقيق.